Negative Acoustic Reflex: An Unusual Finding - JD, Samuel; HS, Gopal; MA, Radha; Murthy, Sudha K (Journal of All India Institute of Speech and Hearing)
The sensitivity of the audiplogical test battery has been greatly enhanced with the introduction of impedance audiometry (Hodgson,1978). Acoustic reflex testing, a part of impedance battery is a reliable diagnostic indicator of various lesions in the auditory system (Wilber and Feldman, 1976)